The impact of a teaching methodology based on the guessing strategy on improving technical performance in complex offensive skills with the foil. (Al-Muthanna Journal of Sport Education Sciences, 2026)
The study aims to prepares and educational curricular accord to inclusion and introduction in improving the level of technical performance of the complex attack skills with foil, and identify to the effectiveness inclusion and introduction in improving the level of technical performance of the complex attack skills with foil. The researchers use the  method experimental for suitability to the natures the problem. In th researchers identified the community, which is the third-year students in the College of Physical Education - Al-Muthanna University for the academic year (2025-2026), numbering (100) students distributed over (5) sections, with (20) students for each section, which are (B-C-D-E-F). As for the sample, and by the random method (lottery), the group (B) was chosen to control group, the works with followed the teachers, and the number of students is (20) representing a percentage of (100%). As for the second experimental group, group (F), which works with the inclusion method, and the number of students is (20) representing a percentage of (100%). The researchers used the appropriation statistical to prose data, in through the results they obtained, it was concluded that the inclusion and input method in  more effectives than the